Customer service : - Lucas, Robert W. (McGraw - Hill, 2005)
Customer Service, Third Edition by Lucas features how-to topics for the customer service professional. It covers the concepts and skills needed for success in business careers, including listening techniques, verbal and nonverbal communication, and use of technology. Emphasis is given to dealing with customer service problems and how to handle conflicts and stress. Insights and tips are also provided for customer service supervisory personnel.